A Fully Synthetic Glycopeptide Antitumor Vaccine Based on Multiple Antigen Presentation on a Hyperbranched Polymer. Issue 15 (12th March 2014) - Glaffig, Markus; Palitzsch, Björn; Hartmann, Sebastian; Schüll, Christoph; Nuhn, Lutz; Gerlitzki, Bastian; Schmitt, Edgar; Frey, Holger; Kunz, Horst
Abstract For antitumor vaccines both the selected tumor‐associated antigen, as well as the mode of its presentation, affect the immune response. According to the principle of multiple antigen presentation, a tumor‐associated MUC1 glycopeptide combined with the immunostimulating T‐cell epitope P2 from tetanus toxoid was coupled to a multi‐functionalized hyperbranched polyglycerol by "click chemistry". This globular polymeric carrier has a flexible dendrimer‐like structure, which allows optimal antigen presentation to the immune system. The resulting fully synthetic vaccine induced strong immune responses in mice and IgG antibodies recognizing human breast‐cancer cells.